STATE BUDGET DEFICIT, ITS CAUSES OF OCCURENCE AND METHODS OF FINANCING (World Economics and Finance Bulletin, 2026)
The article discusses the problem of the state budget deficit, its causes, consequences and the main ways of financing. The article analyzes different economic approaches to deficit management – the Keynesian theory, which assumes the active use of scarcity to stimulate the economy in times of crisis, and the monetarist position, which advocates strict restrictions on government spending. Special attention is paid to the views of A. Laffer on the impact of the tax burden on budget revenues, as well as the concept of Ricardian equivalence. Barro, according to which government borrowing is perceived as deferred taxation. The paper also discusses modern approaches, including the theory of modern monetary theory (MMT), and provides empirical studies by K. Rogoff and K. Reinhart on the impact of high levels of government debt on economic growth.
Keywords: State budget; public debt; deficit financing; tax policy